Smart tourism technologies for the psychological well-being of tourists : a Bangladesh perspective - Gani, Mohammad Osman; Roy, Hiran; Faroque, Anisur R.; Rahman, Muhammad Sabbir; Munawara, Maisha (Emerald, 2023)
Purpose The importance of smart tourism technologies (STTs) has been rising recently, but how STTs are related to tourists’ psychological well-being has got little attention. The study intends to show how STTs increase tourists’ psychological well-being by capitalizing on the theory of Tourism 4.0. The study investigates the associations between the factors of STTs with the perceived benefit and, subsequently, perceived benefit with the psychological well-being of tourists. Moreover, this study also examines the moderating impact of a growth mindset (GM) between perceived benefits (PB) and tourists’ psychological well-being (TPW) in the tourism industry. Design/methodology/approach Using a structured questionnaire, 243 responses were collected through the convenience sampling method. Partial least square structural equation modeling (PLS-SEM) was used for the analysis. Findings Findings show that automation, security/privacy concerns, information accuracy, and personalization are significantly related to the PB of tourists. The results also confirm that a GM moderates the relationship between PB and TPW. Practical implications The results show the social and managerial importance of the perspective of tourism in developing countries. Based on the tourism 4.0 concept, this study presents a theoretical contribution by expanding practical information regarding the link between STTs and psychological well-being. Moreover, the study shows some directions to the tour operator about improving PB and psychological well-being. The notion of tourism 4.0 is a new paradigm that seeks to unlock the psychological well-being of visitors through the hyper-interconnectedness of humans and technologies. Originality/value This study contributes to prior research on technology-based tourism by exploring the uncharted STT variables, PB, GM and psychological well-being. Moreover, the study makes an empirical effort to conceptualize the tourism 4.0 concept on the proposed relationships. Tourist firms should focus on implementing this theory to develop their business.
Keywords: Tourism 4.0; Smart tourism technology; Tourist's psychological well-being; Growth mindset; Perceived benefit; Automation; Personalization; Information accuracy; fi=Kansainvälinen liiketoiminta|en=International Business|